Physiological and psychological health benefits of urban green space in Kuala Lumpur: a comparison between Taman Botani Perdana and Jalan Bukit Bintang - Mohamed Mokhtar, Mohamed Daniel; Abdul Aziz, Nor Akmar; Mariapan, Manohar (Universiti Putra Malaysia Press, 2018)
This study explores physiological and psychological effects of urban green space by using measurements and self-reported psychological responses to an urban park compared to a city environment. Participants of this study were 20 homogenous male students. Taman Botani Perdana, an urban park in Kuala Lumpur, and Jalan Bukit Bintang, a commercial district in the city centre were chosen as the study areas for this study. On the first day, the participants went to Taman Botani Perdana, and to Jalan Bukit Bintang on the second day. In both areas, the participants were instructed to walk along a given route for 20 minutes. Saliva samples were collected before and after walking in both areas along with blood pressure measurements. Self-reported physiological responses were measured before and after each walking session. Results indicated that salivary cortisol concentration significantly increased in the city, whereas no significant change was found in the urban park. Diastolic blood pressure significantly reduced after walking in the urban park. In terms of psychological responses, Total Mood Disturbance among the participants were significantly lower when they were in the urban park compared to the city. Meanwhile, the Positive and Negative Affect Schedule (PANAS) showed that positive effect significantly increased after walking in the urban park, whereas the participants' positive effects significantly reduced after walking in the city. These results indicate that urban green space has positive benefits physiologically and psychologically compared to urban environment.